Evaluation of Digital Simulation Learning Based E-Learning in Smk Negeri 2 Padang - Zaimul Ardi; Syahril Syahril; Muhammad Anwar (International Journal of Educational Dynamics, 2020)
Based on the observation that have done at SMK Negeri 2 Padang, there are some problems on implementation of e-learning based Digital Simulation learning. One of which had never done an evaluation on implementation of e-learning based Simulasi Digital learning. This study aimed to evaluate the component of context, input, process, and product on implementation of e-learning based Digital Simulation learning at SMK Negeri 2 Padang. This research was an evaluation study with CIPP evaluation model (Context, Input, Process, Product). The method was used a mixed method by sequential explanatory. Quantitative data have been collected by quesionner and analyzed with descriptive analysis using Achievement Level Respondents (TPR). Qualitative data have been collected by interviewed and observated, and analyzed with data reduction, data display, and make decisions/verification. The result of this reasearch showed that the component of the context, input, process, and product on implementation of learning based Digital Simulation learning at SMK Negeri 2 Padang was at enought category. The component of process and product should be improved to make the implementation of e-learning based Simulasi Digital learning to be more optimal. The recommended is the implementation of e-learning based Digital Simulation learning can proceed with the improvement at each of its components.